Analysis of Medical Costs of Type 2 Diabetes Mellitus Outpatient Muhammadiyah Hospital North Sumatra - Royyan Ashri; Destanul Aulia; Fazidah Aguslina Siregar (Universitas Muhammadiyah Yogyakarta, 2023)
Type 2 diabetes mellitus and its complications are expensive. Complications are major cost drivers. Of the ten most outpatient diagnoses at Muhammadiyah Hospital, North Sumatra, there was a negative difference between INA-CBGs rates and hospital rates for type 2 diabetes mellitus cases. This study aims to estimate the medical cost, assess the average cost difference, and examine the cost component associated with outpatient type 2 diabetes mellitus. This quantitative analytic research used secondary data on outpatient medical records of type 2 diabetes mellitus patients from May 2019-April 2020. There were 61 samples of medical records. Results showed that the average annual medical cost of outpatient type 2 diabetes mellitus without complication was IDR. 298,177, 8 and IDR. 853,696,7, IDR. 932,341,7, IDR. 938,433.3 if accompanied by macrovascular complications, microvascular complications, and both, respectively. There was a significant difference (p = 0.004) in the mean medical costs per year between the complication groups. Drug costs significantly differed (p = 0.010) between the complication groups. Drug costs are the most expensive and are strongly associated with the medical costs of complicated type 2 diabetes mellitus.